Higher Education New Approaches to Accreditation, Digitalization, and Globalization in the Age of Covid - Waller, Lee; Waller, Sharon (IntechOpen, 2022)
The world of education is experiencing a time of unprecedented change. In our modern, Covid-racked world, educational institutions and their respective delivery methodologies have been forcibly and forever transformed. Most educators realize that these transformations are likely permanent and that procedures and systems of the past will no longer be relevant for the emerging post-Covid educational environment. The future provides countless challenges and great opportunities. Those embracing the transformation will be poised to usher in a new age of educational achievement. They will certainly unleash new educational methodologies, techniques, and strategies. These institutions and educators will chart tomorrow's pathway.